The Influence of Social Capital on Entrepreneurial Success: A Study of Networks and Relationships in MSMEs - Rijal, Syamsu; Utomo, Bekti; Ramdhani, Rahmat (IJBLE Scientific Publications Community Inc., 2024)
This research investigates the influence of social capital on the entrepreneurial success of Micro, Small, and Medium Enterprises (MSMEs) by examining the roles of bonding, bridging, and linking social capital. A mixed-methods approach was employed, including a quantitative survey of 300 MSME owners and qualitative interviews with 20 selected respondents. Descriptive statistics revealed high levels of bonding social capital, significant variability in bridging social capital, and diverse experiences with linking social capital among participants. Regression analyses confirmed the positive impact of bonding, bridging, and linking social capital on different aspects of entrepreneurial success, while structural equation modeling demonstrated their synergistic effects. Thematic analysis of interviews provided deeper insights into how entrepreneurs leverage social capital at various stages of business development. The findings highlight the importance of strategic management of social networks in enhancing MSMEs' ability to innovate, adapt, and achieve sustained growth.